Compound Odontoma in young girl - N., Nurwahida; Sylvyana, Melita; Nurwiadh, R. Agus; Diposarosa, Rizki (Universitas Padjadjaran, 2015)
Introduction. Odontomas are the most common type of odontogenic tumors and generally they are asymptomatic. These tumors are formed from enamel and dentin, and can have variable amounts of cement and pulp tissues. According to radiographic, microscopic, and clinical features, two types of odontomas are recognized: Complex and compound odontomas. Complex odontomas occur mostly in the posterior part of the mandible and compound odontomas in the anterior maxilla. Case Report. A young girl patient, 9 years old came to Department of Oral and Maxillofacial Surgery with a slow growing and asymptomatic swelling in her left posterior mandible for 5 years in his history taking. The panoramic radiograph show a radioopacity and radiolucent lesion at the lower second molar region, with well-corticated limits. An insisional biopsi confirmed as compound odontoma. The surgery performed with simple enucleation and curettage under general anaesthesia. Discussion. Compound odontomas are usually located in the anterior maxilla, over the crowns of unerupted teeth, or between the roots of erupted teeth. In this case report, Compound odontomas are found in the posterior mandible. Conclusion. Compound odontomas in the posterior mandible is a rare. The treatment of odontomas depends on the size of the lesion. The early diagnosis, the treatment of choice is conservative surgical enucleation and curettage and prognosis is excellent.